2015
DOI: 10.1111/1462-2920.12880
|View full text |Cite
|
Sign up to set email alerts
|

Genome and proteome analysis of Pseudomonas chloritidismutansAW‐1T that grows on n‐decane with chlorate or oxygen as electron acceptor

Abstract: Growth of Pseudomonas chloritidismutans AW-1 on C7 to C12 n-alkanes with oxygen or chlorate as electron acceptor was studied by genome and proteome analysis. Whole genome shotgun sequencing resulted in a 5 Mbp assembled sequence with a G + C content of 62.5%. The automatic annotation identified 4767 protein-encoding genes and a putative function could be assigned to almost 80% of the predicted proteins. The distinct phylogenetic position of P. chloritidismutans AW-1 within the Pseudomonas stutzeri cluster beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
(116 reference statements)
3
14
0
Order By: Relevance
“…S2). In line with the expression pattern of cld, a previous proteomic study showed an abundance of chlorite dismutase in strain AW-1 T even when chlorate was replaced by oxygen (19).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…S2). In line with the expression pattern of cld, a previous proteomic study showed an abundance of chlorite dismutase in strain AW-1 T even when chlorate was replaced by oxygen (19).…”
supporting
confidence: 70%
“…S1). Chlorite dismutase is a periplasmic enzyme (19,(33)(34)(35) and hence, utilization of the molecular oxygen derived from chlorite dismutation by oxygenases involved in the further oxidation of the dehalogenated haloalkanoates could be more efficient than using the oxygen from the extracellular environment. To this end, it should be noted that the solubility of chlorate in water (9.93 M at 25°C) is much higher than that of oxygen (0.000269 M at 25°C, under air), suggesting that exponentially growing cells of strain AW-1 T might be oxygen diffusion limited in the case of aerobic cultivation.…”
mentioning
confidence: 99%
“…The only exceptions are the recently discovered 'intra-aerobic' anaerobes which apparently derive oxygen species from utilizing chlorate or nitrite to employ monooxygenases for attacking hydrocarbon substrates (e.g. during anaerobic growth of Candidatus Methylomirabilis oxyfera with methane [Ettwig et al, 2010], gammaproteobacterial strain HdN1 with n -hexadecane [Zedelius et al, 2011] and Pseudomonas chloritidismutans AW-1 T with n -decane [Mehboob et al, 2015]). Accordingly, anaerobic degradation of hydrocarbons involves a variety of intriguing biochemically unprecedented reactions, as indicated by previous microbiological and biochemical research on some model compounds.…”
Section: Biochemical Challenge Of Anaerobic Degradation Of Hydrocarbonsmentioning
confidence: 99%
“…64 The clrABDC cluster of P. chloritidismutans is located on a 12-kb genomic island on the chromosome, and a transposase was found downstream of the clr genes. 13,65 There is only one insert containing the transposase gene, ISPa16, and the organization of cld with a downstream gene for cytochrome c553, an inverted repeat (ISPst12), clrABDC, and genes for an ATPase and a glycosyl transferase family protein are present, similar to Pseudomonas sp. PK.…”
Section: Chlorate Reductionmentioning
confidence: 99%